SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMILIH USAHA WARALABA MAKANAN MENGGUNAKAN METODE TOPSIS - Meri Azmi (Elektron : Jurnal Ilmiah, 2013)
Large number of franchises that will be selected as well as indicators of many criteria, it is necessary to build a decision support system that will help decide which franchise to choose. The model used in the decision support system is a Multiple Attribute Decision Making (MADM) and to perform calculations on the case MADM method in finding the best alternative based on the criteria specified use traditional methods TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) to perform the calculations. TOPSIS method is chosen as the method is based on the concept that the best alternative was chosen not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution.